Hydrogeochemical characteristics and genesis of Hongshuilantang Hot Spring and its water temperature anomalies during the Rushan earthquake swarm in Eastern China - Du, Guilin; Su, Shujuan; Chang, Xiangchun; Ren, Hongwei; Huo, Zhuqing; Zhang, Xiaohui (Frontiers in Earth Science, 2023)
Water temperatures of hot springs close to tectonic fault zones often show some variations before earthquakes, and the analyses of earthquake precursors in hot springs have significant referential meaning for earthquake monitoring and forecasting. In this study, major ion concentrations in Hongshuilantang Hot Spring were measured in 2017 and 2020, respectively, and chemical type was classified into HCO3·SO4-Na type based on hydrochemistry compositions. Hydrogen and oxygen isotope compositions in Hongshuilantang Hot Spring were located near the Global Meteoric Water Line (GMWL), indicating that the recharge source of hot spring is meteoric water. δD and δ18O values were not plotted on the Global Meteoric Water Line (GMWL), and deviations happened to some extent, which suggested that hot spring water underwent water-rock interactions, at the same time, deep circulation water played an important role during the evolution process of thermal water. Water temperature represented a decreasing trend from October 2013 to June 2015 during the period of Rushan earthquake swarm, eastern China. It is inferred that, due to the occurrence of earthquake swarm, regional stress in this area began to release and rebalanced continuously, free water surface appeared in some aquifer, and the seepage of low-temperature underground water in upper aquifer led to the drop of water temperature in the hot spring. Moreover, Hongshuilantang Hot Spring and epicenter of Rushan earthquake swarm are located on the Muping-Jimo seismological fault zone, with same seismotectonic system and some genetic relationships.